Effects of Artificial Intelligence Integration on Design Mindset, Creativity, and Reflection - Amri, Khaerul; Intan Novita Kowaas; Andro Ruben Runtu; Muhajji, Rifky (Journal of Applied Artificial Intelligence in Education, 2025)
Artificial intelligence (AI) improves the efficiency of the design process, helps with fast and accurate data analysis, and aids creativity with innovative ideas. Using a quantitative approach with a cross-sectional design, this study looked at how the incorporation of AI impacts students' creativity, design mindset, and reflection. 96 people responded using an online questionnaire. The results showed that artificial intelligence had a moderate positive effect on design mindset, especially in terms of concept building, problem finding, and design iteration. AI also helped students become more creative, develop imagination, and become more productive. Critical analysis, learning from mistakes, and a deeper understanding of the creative process are enabled by AI. The study found that AI integration can enhance human-machine collaboration to produce more innovative and reflective design outcomes. However, to implement it successfully, a balance between AI automation and human control is required. This study provides insights for educational institutions on how best to utilize AI in learning design and creativity